Extraskeletal Myxoid Chondrosarcoma of the Vulva Confirmed by EWSR1 FISH: A Case Report and Review of the Literature. (16th September 2021) - Salah, Haneen T.; Stivers, Nicole S.; Jarboe, Elke A.; Dodson, Mark K.; Ward, Michael B.
Abstract : Extraskeletal myxoid chondrosarcoma of the vulva is a very rare tumor, with less than 10 cases reported in the literature. We report a case of a 45-yr-old woman with extraskeletal myxoid chondrosarcoma of the vulva confirmed by EWSR1 fluorescence in situ hybridization. Given the unusual site and prominent myxoid morphology, a broad differential diagnosis and a variety of ancillary testing was required. This article aims to review extraskeletal myxoid chondrosarcoma of the vulva, the differential diagnosis of a myxoid spindle cell neoplasm of the vulva, and the diagnostic importance of immunohistochemistry and EWSR1 fluorescence in situ hybridization.